Not-So-North Sea - Reebs, Stephan (Natural history, 2008)
Jan Geert Hiddink of Bangor University in Wales and Remment ter Hofstede of Wageningen University and Research Centre in the Netherlands analyzed the results of yearly bottom trawl surveys. They discovered that since 1985, a temperature hike of almost 3 degrees Fahrenheit has caused the number of bottom-dwelling fish species in the North Sea to increase by half.